2015
DOI: 10.1039/c5ta04773k
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced capacitance of nitrogen-doped hierarchically porous carbide-derived carbon in matched ionic liquids

Abstract: Supercapacitors combine efficient electrical energy storage and performance stability based on fast electrosorption of electrolyte ions at charged interfaces. They are a central element of existing and emerging energy concepts. A better understanding of capacitance enhancement options is essential to exploit the full potential of supercapacitors. Here, we report a novel hierarchically structured N-doped carbon material and a significant capacitance enhancement for a specific ionic liquid. Our studies indicate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
32
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(36 citation statements)
references
References 62 publications
(63 reference statements)
3
32
0
1
Order By: Relevance
“…The polymer based synthesis protocol for SiCN, operating by crosslinking polysilazanes and subsequent pyrolysis, allows the introduction of porosity in various ways. For instance, metal-mediated nanoporosity34 and meso-structuring via sacrificial polyolefin components have been reported35363738.…”
Section: Resultsmentioning
confidence: 99%
“…The polymer based synthesis protocol for SiCN, operating by crosslinking polysilazanes and subsequent pyrolysis, allows the introduction of porosity in various ways. For instance, metal-mediated nanoporosity34 and meso-structuring via sacrificial polyolefin components have been reported35363738.…”
Section: Resultsmentioning
confidence: 99%
“…In the present study, we used a similar approach but varied the organic group to introduce nitrogen via silane to the ceramic material. Nitrogen in the carbide can still be found in the CDC material after chlorine gas treatment, as we know from previous work . We produced CDCs also with another silane to obtain porous carbon materials without nitrogen with a similar pore size distribution (average pore size of 1.6–1.9 nm and 94–99 % of the pore volume relates to pores smaller than 5 nm).…”
Section: Introductionmentioning
confidence: 81%
“…Along with this line of research, Ewert et al. reported that nitrogen‐doping of CDC leads to an enhanced specific capacitance for certain ionic liquids, such as EMIM‐BF 4 , while there was no enhancement for organic electrolytes based on acetonitrile as the solvent . Also, other groups investigated nitrogen‐doped carbon materials made from different precursors and reported high specific energy of up to 64 Wh/kg (measured at a cell voltage of 3.2 V) ,,,.…”
Section: Introductionmentioning
confidence: 96%
“…Ionic conductivities were compared to chitosan/adipic acid and chitosan/acetic acid binary electrolytes. Ewert et al have investigated matching compatibility of various porous N‐doped hierarchical carbon materials with different ionic liquids. They have shown the importance to adapt the IL with the electrode material, more particularly in terms of capacitance and long‐term stability; [EMIm][BF 4 ] and [EMIm][Tf 2 N] were more particularly investigated.…”
Section: Ils For Edlcs and Hybrid Scsmentioning
confidence: 99%